INCIDENCE OF MUSCULOSKELETAL INJURIES IN MALE HANDBALL ATHLETES - Kamonseki, Danilo Harudy; Fonseca, Carlos Luques; Zamunér, Antonio Roberto; Souza, Neemias Adão; Aguiar, Geiseane Gonçalves; Peixoto, Beatriz Oliveira (Journal of Health Care, 2015)
Introduction: Handball is a fast-paced, explosive and contact sport, which requires actions such as jumping,blocking and throwing, considered a high-risk sport, for its occurrence of injuries. Objective: Toverify the incidence of musculoskeletal injuries occurred in a season with handball players. Materials andmethods: It was an observational prospective study, relative the occurrence of musculoskeletal injuries inmale athletes, aged 16 to 20 years, during the 2010 season. Results: The total incidence was 13.06 injuriesper 1000 hours of playing; during matches, 40.81 injuries, and during practices, 8.24. The most affectedregion of the body was the ankle (41,66%), followed by shoulder (25%), knee (12,5%), head (8,33%),hand (41,6%), thigh (4,16%) and elbow (4,16%). Conclusion: The predominant injuries in handballaffects the lower limbs followed by superior ones, although most of injuries were considered mild. Theamount of injuries during practices was higher, but when considered injuries per hour played, matcheswere more harmful.